Pengaruh Luas Lahan, Benih, Tenaga Kerja, Herbisida, dan Pengalaman Berusahatani terhadap Produksi Kacang Tanah di Desa Lindo Kecamatan Wadaga Kabupaten Muna Barat - Wa Ode Risma; Abdul Gafaruddin; La Ode Kasno Arif (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This study aims to determine peanut production in Lindo Village, Wadaga District, West Muna Regency, and determine the effect of land area, seeds, labor, herbicides, and farming experience on peanut production in Lindo Village, Wadaga District, Muna Regency. West. This research was conducted in Lindo Village, Wadaga District, West Muna Regency, from December to February 2022. This research used the census method on a population of all peanut farmers in Lindo Village, totaling 53 families, all of whom were respondents in this study. The data used in this study is quantitative data obtained from two sources: primary data from direct interviews with respondents and secondary data from the Central Bureau of Statistics of West Muna Regency. The dependent variable in this research is peanut production, and the independent variables are land area, seeds, labor, herbicides, and farming experience. Data analysis used descriptive qualitative analysis and Cobb-Douglas function regression analysis. The results showed that (1) peanut production in Lindo Village, Wadaga District, Muna Barat Regency was 39,816 kg/ha with an average of 751.25 kg/ha, and (2) Simultaneously (together) the independent variables, which included area land (X1), seeds (X2), labor (X3), pesticides (X4), and farming experience (X5) have a real influence on peanut production. Partially, land area (X1) and seeds (X2) have a positive and significant influence on peanut farming production, while labor (X3), pesticides (X4), and farming experience (X5) do not affect peanut farming production. Based on the research results, several suggestions can be submitted, namely, farmers to increase farmer production in peanut farming by expanding land, increasing the use of seeds, adjusting the use of herbicides and labor, and increasing the use of inputs to maximize production. The government can provide counseling and guidance, more intensive technical assistance to increase peanut production, and facilities or infrastructure assistance in peanut farming.